2020
DOI: 10.1016/s2214-109x(20)30277-1
|View full text |Cite
|
Sign up to set email alerts
|

Domestic HPV vaccine price and economic returns for cervical cancer prevention in China: a cost-effectiveness analysis

Abstract: Background Coinciding with the release of the first Chinese domestic human papillomavirus (HPV) vaccine Cecolin in 2019, and the substantial advancements in cervical cancer screening technology, we aimed to evaluate the costeffectiveness of the combined strategies of cervical cancer screening programmes and universal vaccination of girls (aged 9-14 years) with Cecolin in China.Methods We did a cost-effectiveness analysis in China, in which we developed a Markov model of cervical cancer to evaluate the incremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 20 publications
1
91
0
Order By: Relevance
“…Among the studies, only two from China reported the use of Gardasil-9 which is relatively costlier given its protection against nine types of HPV while the rest reported using the bivalent or quadrivalent vaccines [54,55]. Beginning in 2020, the fourth HPV vaccine product Cecolin was approved by the Chinese Food and Drug Administration and was found cost-effective in cervical cancer prevention in China [4] where the Cecolin is priced at US dollar 47.7 per dose while the imported Cervarix is priced at US dollar 262 for three doses, Gardasil at US dollar 360 for three doses and Gardasil-9 at US dollar 586 for three doses [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies, only two from China reported the use of Gardasil-9 which is relatively costlier given its protection against nine types of HPV while the rest reported using the bivalent or quadrivalent vaccines [54,55]. Beginning in 2020, the fourth HPV vaccine product Cecolin was approved by the Chinese Food and Drug Administration and was found cost-effective in cervical cancer prevention in China [4] where the Cecolin is priced at US dollar 47.7 per dose while the imported Cervarix is priced at US dollar 262 for three doses, Gardasil at US dollar 360 for three doses and Gardasil-9 at US dollar 586 for three doses [4].…”
Section: Discussionmentioning
confidence: 99%
“…There are four vaccines against the HPV: the quadrivalent (4vHPV) Gardasil approved in 2006, bivalent (2vHPV) Cervarix approved in Abbreviations: 2vHPV, bivalent HPV vaccine; 4vHPV, quadrivalent HPV vaccine; 9vHPV, 9-valent HPV vaccine; CENTRAL, cochrane central register of controlled trials; CI, confidence interval; CIN2+, cervical intra-epithelial neoplasia grade II; EMBASE, excerpta medica dataBASE; GNI, gross national income; HPV, human papillomavirus; LMICs, Low-and middle-income countries; MSM, men having sex with men; RR, relative risk; STROBE, strengthening the reporting of observational studies in epidemiology; US, United States; WHO, World Health Organization 2010, 9-valent (9vHPV) Gardasil-9 approved in 2014 and the bivalent Cecolin approved in China in 2019 [3,4]. All vaccines are effective against the high-risk HPV 16/18 while Gardasil has additional coverage against HPV 6/11 and Gardasil-9 against HPV 6/11/31/33/45/52/ 58 [3].…”
Section: Introductionmentioning
confidence: 99%
“… 43 Recently, as the first Chinese domestic-made 2-valent HPV vaccine (Cecolin, Innovax, Xiamen, China) was approved by Chinese FDA, additional efforts should be taken to relieve hesitation regarding the vaccine and use the opportunity to expand vaccine supply and reduce vaccine prices. 44 , 45 If feasible, HPV vaccines for young girls should be guaranteed initially, followed by a “catch-up” vaccination program for young women, and the government should finally integrate HPV vaccination into the national immunization program.…”
Section: Discussionmentioning
confidence: 99%
“…In each model, the retailer confronts a random demand sales season, which is highly dependent on the pricing factor, noting that this assumption is consistent with the reality of many situations, such as over-the-counter medicines and self-funded vaccines (e.g., HPV vaccines) ( Zou et al, 2020 ). As discussed in Sarmah, De Giovanni, and De Giovanni (2020) and analyzed by Ching (2010) , the price swings between patented and generic drugs are a key driving force of consumers’ buying decisions in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 92%